2015
DOI: 10.1016/j.pbiomolbio.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty quantification of fast sodium current steady-state inactivation for multi-scale models of cardiac electrophysiology

Abstract: Perhaps the most mature area of multi-scale systems biology is the modelling of the heart. Current models are grounded in over fifty years of research in the development of biophysically detailed models of the electrophysiology (EP) of cardiac cells, but one aspect which is inadequately addressed is the incorporation of uncertainty and physiological variability. Uncertainty quantification (UQ) is the identification and characterisation of the uncertainty in model parameters derived from experimental data, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 38 publications
3
59
0
Order By: Relevance
“…The cell-specific models outperformed a model constructed using averaged data from multiple cells/experiments, in line with the 'failure of averaging' discussed in Golowasch et al (2002) and the problems of fitting to averaged summary curves outlined in Pathmanathan et al (2015). Our inactivation protocol (Pr4) showed that it is possible for models to fit some (or all) summary curves well, without necessarily replicating the underlying current traces with less error.…”
Section: Discussionsupporting
confidence: 64%
“…The cell-specific models outperformed a model constructed using averaged data from multiple cells/experiments, in line with the 'failure of averaging' discussed in Golowasch et al (2002) and the problems of fitting to averaged summary curves outlined in Pathmanathan et al (2015). Our inactivation protocol (Pr4) showed that it is possible for models to fit some (or all) summary curves well, without necessarily replicating the underlying current traces with less error.…”
Section: Discussionsupporting
confidence: 64%
“…() and the problems of fitting to averaged summary curves outlined in Pathmanathan et al . (). Our inactivation protocol (Pr4) showed that it is possible for models to fit some (or all) summary curves well, without necessarily replicating the underlying current traces with less error.…”
Section: Discussionmentioning
confidence: 97%
“…Such approach, which has not been pursued to date in the cardiac electromechanics community, will need an orchestrated effort between the modeling and experimental teams, as experimental data should thoroughly address and quantify the measurement error as well as the variability inherent to biological samples, and report it in terms of probability distributions that can be properly incorporated in uncertainty quantification analyses. First steps towards a UQ analysis of a cardiac electrophysiology model that follows such approach has been recently reported in Pathmanathan et al, so we expect this attempts to permeate to the electromechanical interaction in the near future, as experimental parameter data reported in probabilistic terms becomes available. Another limitation of this work is the introduction of uncertainty only in the input parameters.…”
Section: Discussionmentioning
confidence: 99%